As “medicinas heréticas” e o holismo francês na primeira metade do século XX - Thomaz, Luciana Costa Lima (2016)
Along the first decades of the twentieth century European and North American doctors became increasingly interested in medical practices rated heterodox and that overall sought to develop a more humane approach to medicine. Later on such practices became known as holistic, for their attempt to take all aspects of human beings into consideration. In France, that movement gained particular momentum in the interwar period and acquired peculiar features that distinguished it from the rest of Europe, Germany in particular, where medical holism was firmly consolidated by that time. Several of the most outstanding French holistic doctors coauthored a book entitled Médecine officielle et médecines hérétiques, published in 1945. This book can be seen as a manifesto against the contemporary official medicine, which according to the authors had surrendered to the evils of the modern civilization. Taking that book as point of departure, our analysis sought to understand the epistemological dialogue established between the holistic and the official medicines within the context circumscribed by the main lines of thought in the beginning of the twentieth century